Pengembangan Game Teka-Teki Silang Berbasis Mobile Interaktif Bertingkat untuk Meningkatkan Kemampuan Berhitung Siswa Sekolah Dasar - Sela Taramita; M Riski Qisthiano (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study developed the MathCross Adventure application, a mobile-based arithmetic crossword puzzle game for elementary school students, using the R&D approach with the ADDIE model. In this study, the stages were implemented up to Implementation and Formative Evaluation (not summative evaluation). Validation was carried out by two subject matter experts/elementary school mathematics teachers and one learning media expert, resulting in an average feasibility of 88.8% (very feasible category). A limited trial was conducted at SD Negeri 27 Banyuasin with 20 sixth-grade students; the results showed the application was easy to use, engaging, and supported learning engagement through its tiered level features, leaderboard, and instant feedback. These findings confirm the product's formative feasibility for use in arithmetic learning. However, summative effectiveness (statistical improvement in arithmetic ability) has not been tested; further research is recommended using the N-Gain test or paired t-test with a larger sample to empirically verify the learning impact.